IMPACT OF CHANGING WORKING ENVIRONMENT ON MENTAL HEALTH AMONG EDUCATORS DUE TO PANDEMIC COVID-19: A LITERATURE REVIEW - Zulkifle, Nurul Atiqah; Mat Isa, Siti Sarah; Mohd Sam, Mohd Fazli; Jamaludin, Fazdlina; Shari, Norhasimah; Zuraidi, Siti Nur Afiza (Jurnal ’Ulwan, 2022)
The SARS-CoV-2 (COVID-19) pandemic has resulted in changes to the working arrangements especially for education sector in the country. From primary school up to tertiary level, education sector has to shifted temporarily from traditional teaching and learning process to online teaching and learning process. Many educators were struggling to continue with their new routine and try to be mentally strong with the new adjustment. Some of them have little knowledge and were unable to cope with the changes. Even though Malaysia has move to the endemic phase, the education industry has started to shifted the delivery method to adapt with Volatility, Uncertainty, Complexity, Ambiguity (VUCA) environment which surrounding the education landscape as well as to accelerate the transition towards education Industrial Revolution 4.0. In order to maintain the quality of teaching and learning process, it is important to discuss the impact of changing work environment on mental health among educators. This research tries to explore the impact of changing working environment on mental health among educators through literature review. Findings on this research can be used by education sector in designing the best method that can minimize the impact of changing working environment on mental health among educators.